2015
DOI: 10.1021/acs.nanolett.5b01167
|View full text |Cite
|
Sign up to set email alerts
|

Self-Extinguishing Lithium Ion Batteries Based on Internally Embedded Fire-Extinguishing Microcapsules with Temperature-Responsiveness

Abstract: User safety is one of the most critical issues for the successful implementation of lithium ion batteries (LIBs) in electric vehicles and their further expansion in large-scale energy storage systems. Herein, we propose a novel approach to realize self-extinguishing capability of LIBs for effective safety improvement by integrating temperature-responsive microcapsules containing a fire-extinguishing agent. The microcapsules are designed to release an extinguisher agent upon increased internal temperature of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 48 publications
0
82
0
Order By: Relevance
“…Introduction of as timuli-responsivep olymer coating onto the polyolefin separators is an emerging approach to enhance the safety performance of the separator.Aself-extinguishing separatorw as proposed recently. [24] This novel separator consisted of aP El ayer and am icrocapsule coating. The coated microcapsules contained (1,1,1,2,2,3,4,5,5,5-decafluoro-3methoxy-4-(trifluoromethyl)-pentane) (DMTP), which is fire distinguishing ( Figure 2A).…”
Section: Advanceds Eparators For Li-ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of as timuli-responsivep olymer coating onto the polyolefin separators is an emerging approach to enhance the safety performance of the separator.Aself-extinguishing separatorw as proposed recently. [24] This novel separator consisted of aP El ayer and am icrocapsule coating. The coated microcapsules contained (1,1,1,2,2,3,4,5,5,5-decafluoro-3methoxy-4-(trifluoromethyl)-pentane) (DMTP), which is fire distinguishing ( Figure 2A).…”
Section: Advanceds Eparators For Li-ion Batteriesmentioning
confidence: 99%
“…(A) Pictures of the electrolytes with different additives after ignition using aconventional lighter (left) and as chematicshowing the fabricationp rocess of the DMTP microcapsule-coated separator and its working mechanism (right);r eproduced with permission from Ref [24]. copyright 2015 American Chemical Society.…”
mentioning
confidence: 99%
“…[14] In another form of additive,Y im et al reported the use of microencapsulated fire-extinguishing agent, dimethylthiophosphate (DMTP), which was able to absorb heat from the LIB at elevated temperatures. [19] In another reported use of thermoresponsive polymer, Baginska et al coatedp olyethylene (PE) microspheres ontot he anode,w hich melts at 110 8C, preventing furtheri onic conduction between the electrodes. [20,21] Most recently,C hen et al adapted thermoresponsive PE and made ac onductive film by mixing spiky Ni/Gr particles.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] Factors including the battery materials, 18,19 states of charge (SOC), 20,21 battery states, 22 heating modes, 23 ambient pressures, 13 battery modules, 24 and incident heat fluxes, 8 impacting the fire behavior of LIBs were focused. [9][10][11][12][13][14][15][16][17] Factors including the battery materials, 18,19 states of charge (SOC), 20,21 battery states, 22 heating modes, 23 ambient pressures, 13 battery modules, 24 and incident heat fluxes, 8 impacting the fire behavior of LIBs were focused.…”
mentioning
confidence: 99%
“…Previous researches on thermal behavior and fire hazards of LIB have been performed at small format battery. [9][10][11][12][13][14][15][16][17] Factors including the battery materials, 18,19 states of charge (SOC), 20,21 battery states, 22 heating modes, 23 ambient pressures, 13 battery modules, 24 and incident heat fluxes, 8 impacting the fire behavior of LIBs were focused. Ribiere et al 25 identified and quantified the toxic emissions (NO, HCl, HF, etc.)…”
mentioning
confidence: 99%